The structure, drivers and policy implications of the European carbon footprint. (8th April 2020) - Wood, Richard; Neuhoff, Karsten; Moran, Dan; Simas, Moana; Grubb, Michael; Stadler, Konstantin
ABSTRACT: Policy to reduce the European Union's (EU) carbon footprint needs to be grounded in an understanding of the structure and drivers of both the domestic and internationally traded components. Here we analyse consumption-based emission accounts (for the main greenhouse gases (GHGs)) for the EU, focusing on understanding sectoral contributions and what changes have been observed over the last two decades, including the role of trade. The EU28 has reduced its overall GHG footprint by 8% over the two decades, mainly due to the use of more efficient technology, both at home and abroad. Emissions embodied in imports, which make up one-third of the EU28 GHG footprint, grew strongly until 2008 but have stabilized in volume since. Foreign production has been more emissions intensive than if goods were produced in the EU. However, the overall contribution of this effect is small, offset by much larger (global) technological improvements and growths in consumption. Hence the focus should now be on accounting and responsibility for enacting change, not the global impact of trade. Finally, the inclusion of non-CO2 GHGs in the analysis shows their importance in the traded element, particularly for the mining and agricultural sectors. Key policy insights The total EU carbon footprint has reduced since 2007, but at a slower rate than production-based emissions, and rarely faster than GDP growth. Consumption growth has had a much greater impact on the EU carbon footprint than the offshoring of production. Trade in both directions (imports and exports) is important for the manufacturing sector. The data does not support claims of wholesale 'de-industrialisation' but rather reflects increased trade intensity related to specialization. Several (but not all) of the major sources of net embodied imports are largely unavoidable consequences of European consumption because the primary production activities (e.g. mining and significant shares of agricultural) could not realistically occur within the EU.